PENERAPAN PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS VI MIN RUKOH BANDA ACEH - Syahidan Nurdin (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
The purpose of learning science in the KTSP is to develop process skills to investigate the environment, solve problems and make decisions. Students' ability in science process skills will affect students' abilities in learning. Research has been carried out on improving science process skills in learning through the application of group investigations of class VI students at MIN Rukoh Banda Aceh City. This research raises the issue of